Revision of Dinosaur Ichnotaxa from the La Matilde formation (Middle Jurassic), Santa Cruz Province, Argentina - de Valais, Silvina (2011)
An ichnological assemblage from the Middle Jurassic La Matilde Formation at Estancia Laguna Manantiales, Santa Cruz Province, Argentina, is exceptional both in diversity and abundance. It includes four dinosaurian ichnotaxa (Wildeichnus, Grallator, and the endemic Delatorrichnus and Sarmientichnus), the mammalian Ameghinichnus, several vertebrate tracks of uncertain ichnogeneric assignation and invertebrate and root cavities. Because of its importance, an updated ichnotaxonomic revision and a detailed study are needed. In this contribution, the dinosaur ichnogenera are revised and emended diagnoses of three of them are provided. Recorded together with ichnogenera originally named by Casamiquela —Delatorrichnus, Sarmientichnus and Wildeichnus— is the cosmopolitan Grallator. A few tracks of dubious assignation are described. Casamiquelichnus Coria and Paulina Carabajal, 2004, from the same locality, is a junior synonym of Sarmientichnus. The paleocommunity represented by the La Matilde ichnofauna was dominated by small-bodied species with high regenerative and resettling capacity.